Integrasi Teknologi dan Psikometri: Pengembangan Alat Diagnostik Berbasis Aplikasi Menggunakan Model Partial Credit untuk Mengidentifikasi Miskonsepsi Siswa - Nurhasanah; Zul Hidayatullah; Hajra Yansa; Moh. Badrus Sholeh Arif; Muh Asriadi (Jurnal Penelitian Pendidikan IPA, 2025)
Misconceptions in science learning remain a major barrier to students’ conceptual understanding, while traditional assessments often fail to detect them effectively. This study aimed to develop PhyTestApp, an app-based diagnostic tool that integrates the Partial Credit Model (PCM) under Item Response Theory (IRT) to uncover student misconceptions in science. A research and development design was employed, involving expert validation, limited trials, and psychometric testing. The two-tier items were designed to capture both factual knowledge and reasoning. Findings indicated that the instrument met psychometric requirements, with items demonstrating good fit and functioning across different levels of student understanding. Usability testing also showed positive responses from students and teachers regarding clarity, content relevance, and technical operation. Overall, PhyTestApp provides a reliable and practical diagnostic tool that facilitates immediate feedback and supports more targeted science instruction. These results highlight the potential of combining psychometric modeling with mobile technology to improve the quality of science education and more effectively address misconceptions in line with 21st-century learning goals.